Assessing the Role of Faith-Inspired Primary and Secondary Schools in Africa : Evidence from Multi-Purpose Surveys - Tsimpo, Clarence; Wodon, Quentin (Taylor and Francis, 2014)
What is the share of students attending faith-inspired schools (FISs) in Africa? Do FISs reach the poor in priority? How much do they cost for households? And how do FISs compare with public schools and private secular schools in these areas? This article provides tentative answers to these questions using evidence from multi-purpose household surveys.